From a television viewer to a digital consumer: the influence of sports idols on the formation of consumer mindset - Penezić, Slobodan M; Ćitić, Tatjana (Sociološki pregled, 2026)
The development of new technologies, video streaming platforms, social media, and complex marketing networks has transformed the traditional TV viewer into a global consumer. At the same time, in the field of sports, elite athletes have become influencers whose power in promoting and selling a brand is considerable, owing to the credibility they have built within a world of discipline and achievement. In doing so, they influence not only a loyal audience but also the broader population. In addition to these macro-influencers, this study will also examine micro-influencers, identified by social media algorithms as influential within specific niches relevant to digital marketing. We start from the assumption that the mediatization of sports transforms sports idols into symbolic capital of high marketing and cultural significance, while simultaneously fostering the emergence of a contemporary society of the spectacle. The research is based on a qualitative, theoretical-analytical approach and an interdisciplinary synthesis of insights from media studies, the sociology of sports, and marketing, employing the critical content analysis, the comparative analysis of brand ambassadors, case studies, and deductive reasoning. The aim is to demonstrate how the mediatization of sports and the role of idols as bearers of symbolic capital shape consumer awareness in the digital environment.
Keywords: sports idols; television; Internet marketing; mediatization; society of the spectacle